The Influence of Creatine Monohydrate on Strength and Endurance After Doing Physical Exercise With Maximum Intensity - Nabawi, Asrofi Shicas; Setijono, Hari; Muhammad, Muhammad (Universitas Negeri Semarang (Unnes), 2017)
The purpose of this study was: (1) to analyze the effect of creatine monohydrate to give strength after doing physical exercise with maximum intensity, towards endurance after doing physical exercise with maximum intensity, (2) to analyze the effect of non creatine monohydrate to give strength after doing physical exercise with maximum intensity, towards endurance after doing physical exercise with maximum intensity, (3) to analyze the results of the difference by administering creatine and non creatine on strength and endurance after exercise with maximum intensity. This type of research used in this research was quantitative with quasi experimental research methods. The design of this study was using pretest and posttest control group design, and data analysis was using a paired sample t-test. The process of data collection was done with the test leg muscle strength using a strength test with back and leg dynamometer, sit ups test with 1 minute sit ups, push ups test with push ups and 30 seconds with a VO2max test cosmed quart CPET during the pretest and posttest. Furthermore, the data were analyzed using SPSS 22.0 series. The results showed: (1) There was the influence of creatine administration against the strength after doing exercise with maximum intensity; (2) There was the influence of creatine administration against the group endurance after doing exercise with maximum intensity; (3) There was the influence of non creatine against the force after exercise maximum intensity; (4) There was the influence of non creatine against the group after endurance exercise maximum intensity; (5) The significant difference with the provision of non creatine and creatine from creatine group difference delta at higher against the increased strength and endurance after exercise maximum intensity. Based on the above analysis, it can be concluded that the increased strength and durability for each of the groups after being given a workout.